MENINGKATKAN KETERAMPILAN PERILAKU ASERTIF MELALUI PENERAPAN DESAIN PEMBELAJARAN BERBASIS ADLX DENGAN PENDEKATAN TERPADU BAGI SISWA KELAS VIII SMPIT ABU BAKAR YOGYAKARTA - Utami, Suwi Wahyu; Kusumawati, Endah Tri; Lestari, Yayuk Sri (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to improve assertive behavior skills through implementing ADLX-based learning design with a terpadu approach for class VIII D students at SMPIT Abu Bakar Yogyakarta. The research approach uses a classroom action research design carried out in two cycles. The stages in this research consist of 2 cycles, each cycle there are four research steps, namely planning, action, observation and reflection. The research instruments were questionnaires and observations. The data analysis technique uses non-parametric quantitative data analysis, using Wilcoxon matched-pair test analysis for paired data. The research results showed that there was an increase in each cycle with initial data by score of 86, cycle 1 increased 102 and cycle 2 increased 112. Pretest was 71.7%, then posttest was 85.0% and posttest 2 was 93.3%. The increase was 13.3% after cycle 1 and cycle 2 have been applied, it increased to 21.7%. The aspect of assertive behavior also increased, namely the aspect of the ability to act based on self-esteem increased by 23%, the aspect of considering other people's points of view by 19%. The aspect of expressing positive thoughts and feelings is 26% and the aspect of controlling actions and being responsible is 13%.